Recurring outburst floods from drained lakes: an emerging Arctic hazard. Issue 7 (27th February 2020) - Arp, Christopher D; Jones, Benjamin M; Hinkel, Kenneth M; Kane, Douglas L; Whitman, Matthew S; Kemnitz, Richard
Abstract : New development in regions with rapidly changing climates may experience unforeseen hazards. Thermokarst lakes (bodies of freshwater that collect in depressions formed by thawing permafrost) cover 20% of Arctic lowlands and are naturally prone to causing catastrophic flooding. Cumulative lake drainage over time has resulted in up to 60% landscape coverage by drained thermokarst lake basins (DTLBs). Although the impacts of lake drainage on ecosystems and infrastructure have long been considered a potential hazard, these occurrences are usually viewed as one‐time events. However, recent observations in northern Alaska highlight a previously unrecognized threat: annually recurring snow‐dam outburst floods from DTLBs. Each winter, blowing snow fills DTLB drainage gullies, impounding meltwater in the spring and – upon snow‐dam failure – releasing downstream floods. Data collected from 14 DTLBs in Alaska reveal a wide range in flood peaks, many of which exceed river flood events, providing a missing link in Arctic ecosystem hydrology. Projected snowier winters may result in even larger snow‐dam outbursts from DTLBs, adding uncertainty to future risk assessments. If climate change also drives enhanced lake drainage, we predict even more sporadic and higher magnitude floods, with implications for downstream ecosystems and human infrastructure as development pushes into the Arctic lowlands.